Management of grossly decayed primary anteriors using various intracanal post systems: A clinical study - Manjul Mehra; Rashu Grover; Inder Kumar Pandit; Nikhil Srivastava; Neeraj Gugnani; Monika Gupta (Wolters Kluwer Medknow Publications, 2016)
Purpose: The aim of the present study was to clinically evaluate and compare the efficacy and retention of various types of intracanal posts in the restoration of grossly decayed deciduous anterior teeth. The various posts used were polyethylene post, glass post, and composite post. Materials and Methods: A total number of 16 patients with 45 grossly decayed primary anterior teeth were selected. After biomechanical preparation and obturation, patients were randomly divided on the basis of posts to be used into three groups (Group I: Polyethylene post; Group II: Glass post, and Group III: Composite post). Then, space was created in the obturated canal and posts were placed, followed by core build up. Results: After an interval of 12 months, 86.67% of the teeth exhibited complete retention of the post restored with polyethylene post (P > 0.005) and 93.3% of the teeth exhibited complete retention of the post that were restored with glass post (P > 0.005) whereas only 60% of the teeth exhibited complete retention of the post that were restored with composite post (P< 0.005). Only 20% of the teeth exhibited marginal discoloration in both Groups I and III and 13.33% in Group II and this was nonsignificant. Conclusion: Both glass post and polyethylene post proved to be effective. Glass post showed the maximum retention and marginal adaptation followed by polyethylene post. Thus, it appears to be of potential interest for use especially in clinical pediatric dentistry.